MEMBANGUN SEKOLAH UNGGUL (Perspektif Pendidikan Karakter Berbasis Budaya Sekolah) - Bahrus Surur; journal journal (STIT Muhammadiyah Paciran Lamongan, 2019)
Abstract Since decades ago, education in Indonesia a lot of emphasis on the acquisition, development and improvement of the quality of human resources is based on intellectual intelligence or IQ. The ingenuity and intelligence of a learner or student is measured by the ability to master the subject matter academically in school. For children w ho are morally good not considered intelligent, because academically not master. He is still considered stupid. The ranking was measured based on the academic value only. The issue now is, first, what is meant by the so - called character education as a solu tion to the deterioration of this nation? Second, what character education linkages with the school culture? Third, how to implement the planting of moral values and the spirit of life as the core of character education in the school culture? As well as in the form of school culture that is how that can be applied to learners.